Mongolia : Report on the Observance of Standards and Codes-Fiscal Transparency. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides an assessment of fiscal transparency practices in Mongolia against the requirements of the IMF Code of Good Practices on Fiscal Transparency. This paper analyzes the government's participation in the financial and nonfinancial sectors of the economy. Executive Directors appreciated the achievements, and stressed the need for improvements in the areas of fiscal transparency. They emphasized the need for addressing weaknesses of fiscal data, maintaining a legal framework for fiscal control, and strengthening the audit mechanism.